LASER-ASSISTED CROWN LENGTHENING: CLINICAL EFFICACY AND ADVANTAGES OVER CONVENTIONAL TECHNIQUES (SYSTEMATIC REVIEW) - Rachmasari Rieska; Tadjoedin Fatimah Maria (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Crown lengthening is a widely recognized dental procedure with both aesthetic and functional purposes. It involves the reduction of periodontal hard and soft tissues to obtain supracrestal tooth length, resulting in longer clinical crowns and adequate supracrestal tissue attachment. Laser therapy has emerged as a promising alternative that is currently developing in the field of periodontics and offers several advantages. This review aims to synthesize the current research on the clinical efficacy of laser-assisted crown lengthening procedures and highlight their advantages over conventional methods. Review: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a comprehensive search was conducted in electronic databases PubMed, Scopus, Embase, and Google Scholar for human studies published from 2017 to April 2023. Out of 213 identified and screened studies, three original articles were included in the analysis. Two clinical trial studies used Er,Cr:YSGG while one study used Er:YAG for crown lengthening procedures involving gingiva and alveolar bone reduction, with a 3-month follow-up period. Compared to conventional crown lengthening, the laser-assisted approach showed comparable increases in clinical crown length. However, the laser-assisted group demonstrated better gingival margin stability, improved soft tissue healing, and minimal damage to adjacent tissues. Furthermore, there was a statistically significant lower bacterial load and less post-surgery pain with laser-assisted crown lengthening compared to the conventional method. Conclusion: In cases where both gingival and bone reduction are required, laser-assisted crown lengthening using Er,Cr:YSGG and Er:YAG can be considered a minimally invasive alternative with several advantages over conventional procedures.